A Chinese Precursor to the Digital Sovereignty Debate: Digital Anti-Colonialism and Authoritarianism from the Post–Cold War Era to the Tunis Agenda. Issue 4 (28th October 2022) - Cong, Wanshu; Thumfart, Johannes
Abstract: Governments all over the world are constructing discourses of digital sovereignty. However, the history of this concept is understudied. This paper delves into the Chinese academic publications from 1994 to 2005, where concepts such as "network/cyber sovereignty" (网络主权) and "information sovereignty" (信息主权) began to emerge. The period is marked by the introduction of the internet in China in 1994 and the 2005 Tunis Agenda, a pivotal moment in the internationalization of demands for sovereignty over the internet. By reconstructing the post–Cold War geopolitical, economic, cultural, ideological, and regulatory context of the examined publications, we highlight the academic discourse as forming part of a sociotechnical imaginary of digital sovereignty, which is characterized by a peculiar mixture of the explicit critique of "cyber colonialism" (网络殖民主义), authoritarian positions, and the embrace of digitalization and its possibilities.